The New Frontier: Religion in America’s National Space Rhetoric of the Cold War Era - Swanson, Glen E. (Religions, 2020)
The origins and use of national space rhetoric used by NASA, the US government, and the media in America began during the Cold War era and relied, in part, on religious imagery to convey a message of exploration and conquest. The concept of space as a “New Frontier” was used in political speech, television, and advertising to reawaken a sense of manifest destiny in postwar America by reviving notions of religious freedom, courage, and exceptionalism—the same ideals that originally drove expansionist boosters first to the New World and then to the West. Using advertisements, political speeches, NASA documents, and other media, this paper will demonstrate how this rhetoric served to reinforce a culture held by many Americans who maintained a long tradition of believing that they were called on by God to settle New Frontiers and how this culture continues to influence how human spaceflight is portrayed today.